PREVENTION OF DENTAL CARIES AND ENAMEL REGENERATION USING MODERN MINIMALLY INVASIVE APPROACHES (Eureka Journal of Health Sciences & Medical Innovation, 2026)
This article examines minimally invasive approaches to the prevention of dental caries and enamel regeneration. Non-operative methods, including fluorides, CPP–ACP, NovaMin, and β-TCP, aim to control the caries process through remineralization. The biomimetic peptide P11-4 promotes enamel mineral recovery by facilitating hydroxyapatite crystal formation in the subsurface layer. These approaches preserve tooth structure and effectively prevent caries progression.
Keywords: Dental caries, minimally invasive methods, remineralization, biomimetics, enamel regeneration, CPP–ACP, β-TCP, fluorides.